Gulf wireworm, Conoderus amplicollis (Gyllenhal) (Insecta: Coleoptera: Elateridae) - Mohammad Razzak; Dakshina Seal (EDIS)
Larvae of click beetles are known as wireworms because of their wire like appearance. The Gulf wireworm, Conoderus amplicollis, is a polyphagous pest mostly found in soil with high organic matter. In the southeastern United States, it is an important pest of sweet potato and can be found in all growing regions irrespective of soil types.